Atlantic Slavery, Atlantic Freedom: George Washington, Slavery, and Transatlantic Abolitionist Networks - Furstenberg, François (The William and Mary Quarterly, 2011)
Abstract What can a volume from George Washington’s library say about his opinion of slavery or about abolitionism more generally in the late eighteenth century? A great deal, it turns out. Understood both as an intellectual and material artifact and approached from the entangled perspectives of the history of the book and transatlantic abolition, one single bound pamphlet volume brings a new Washington into focus. It locates him in the context of an international debate about slavery connecting British pamphleteers, Parisian salons, and transatlantic friendships; follows European travelers as they disseminated books and pamphlets and carried on conversations on both sides of the Atlantic; and leads eventually to the broader contexts of imperial rivalry and international abolitionism. Set in this context, Washington emerges as a thinker well within the broad mainstream of European opinion about abolition. But even more this new view of Washington helps elucidate the international networks of abolitionist writing and activism that shaped the movement during the age of Atlantic revolutions. Web supplement: http://oieahc.wm.edu/wmq/Apr11/furstenberg.html

When the United States spoke French: five refugees who shaped a nation - Furstenberg, François (The Penguin Press, 2014)
"In 1789, as the French Revolution shook Europe to the core, the new United States was struggling for survival in the face of financial insolvency and bitter political and regional divisions. When the United States Spoke French explores the republic's formative years from the viewpoint of a distinguished circle of five Frenchmen taking refuge in America. When the French Revolution broke out, these men had been among its leaders. They were liberal aristocrats and ardent Anglophiles, convinced of the superiority of the British system of monarchy and constitution. They also idealized the new American republic, which seemed to them an embodiment of the Enlightenment ideals they celebrated. But soon the Revolutionary movement got ahead of them, and they found themselves chased across the Atlantic. François Furstenberg follows these five men – Charles-Maurice de Talleyrand-Périgord, Napoleon's future foreign minister; theorist/reformer Rochefoucauld, the duc de Liancourt; Louis-Marie Vicomte de Noailles; Moreau de Saint-Méry; and Constantin-François Chasseboeuf, Comte Volney – as they left their homes and families in France, crossed the Atlantic, and landed in Philadelphia – then America's capital, its principal port, and by far its most cosmopolitan city and the home of the wealthiest merchants and financiers. The book vividly reconstructs their American adventures, following along as they integrated themselves into the city and its elite social networks, began speculating on backcountry lands, and eventually became enmeshed in Franco-American diplomacy. Through their stories, we see some of the most famous events of early American history in a new light, from the diplomatic struggles of the 1790s to the Haitian Revolution to the Louisiana Purchase in 1803. By the end of this period, the United States was on its way to becoming a major global power. Through this small circle of men, we find new ways to understand the connections between U.S. and world history, and gain fresh insight into American history's most critical era. Beautifully written and brilliantly argued, When the United States Spoke French offers a fresh perspective on the tumultuous years of the young nation, when the first great republican experiments were put to the test"–
Keywords: 18th century; Aristocracy (Social class); France; French; HISTORY / Europe / France; HISTORY / United States / Revolutionary Period (1775-1800); History; History Refugees; Pennsylvania Philadelphia; Philadelphia (Pa.); Political refugees; Revolution; 1789-1799; Social conditions

Piédestal et indépendance féminine : la hiérarchie de genre sudiste pendant la guerre civile et la Reconstruction - Dansereau, François (Université de Montréal, 2008)
Keywords: Classes sociales; Confederate States of America; Culture populaire; Femmes de l'élite; Guerre et société; Memory; Mémoire; Plantation life; Popular culture; Race and ethnicity; Race et ethnicité; Social classes; Southern states; Upper class women; Vie dans les plantations; War and society; États confédérés; États du sud

Transformations sociales chez les Cherokees, 1794-1827 - Laramée, François Dominic (Université de Montréal, 2014)
Bouleversements démographiques, pressions assimilatrices, défaites militaires et rivalités territoriales : ce mémoire étudie les transformations que connaît la société Cherokee sous l’impulsion de ces forces au cours du «long XVIIIe siècle» qui débute avec l’intensification des contacts avec les colons anglais vers 1700 et qui se termine avec la déportation des Cherokees vers l’Indian Territory, dans l’actuel Oklahoma, à la fin des années 1830. Son regard porte principalement la centralisation des institutions politiques, la transformation des règles qui définissent l’appartenance à la nation, et l’évolution des rôles des genres dans la famille et dans l’économie pendant la période entre la signature du traité de paix de 1794 et l’adoption par les Cherokees d’une Constitution fortement inspirée de celle des États-Unis, en 1827.
Keywords: 18th century; 19th century; Cherokee; Gender studies; Histoire; Histoire autochtone; Histoire du genre; Histoire politique; History; History - United States / Histoire - États-Unis (UMI : 0337); Identity; Identité; Native American history; Native Americans; Political history; United States; XIXe siècle; XVIIIe siècle; États-Unis

Introduction: Entangling the Quebec Act - Hubert, Ollivier; Furstenberg, François (Entangling the Quebec Act: Transnational Contexts, Meanings, and Legacies in North America and the British Empire, 2020)
Accepted: 2021-03-16T17:45:23Z

Liberation from Below : the Caribbean Conference Committee of Montreal and the global new left - Austin, David (Université de Montréal, 2008)
Keywords: Black; Canada; Caraïbéenne; Carribbean; New left; Noir; Nouvelle gauche

Liberté, égalité, fraternité, la place des réfugiés de Saint-Domingue et de la France à La Nouvelle-Orléans vue par les correspondances d’Henri de Ste Gême (1767-1842) - Cadorette, Mickaël (Université de Montréal, 2017)
During his lifetime from 1767 to 1842, Henri de Ste-Gême, an émigré of the French Revolution migrated to the French colony of Saint-Domingue where he fought for both the British and the Republican armies. Afterwards he migrated to Cuba and to New Orleans where he fought under the command of General Andrew Jackson during the Battle of New Orleans and was praised for his service. Henri de Ste-Gême returned to France in 1818 and imparted the Louisiana business to his friends. Notably, it was Jean Boze who would later write chronicles about what was going on in New Orleans. This correspondence serves as a witness to the evolution of New Orleans during the 1830s at a moment where the Francophones went from being a majority to a minority. Further, this Americanization and diversification of the population is described by Boze, a Saint-Domingue refugee, who devotes special attention to this part of the population and to their relationship with other francophones during that time period. Furthermore, Boze’s correspondence reveals France’s importance in American Louisiana particularly in the 1830s, when New Orleans formed an enclave in the French Atlantic world and when the French-speaking population developed a hybrid identity.
Keywords: 19th century; Atlantic history; Cuba; France; French Atlantic; Henri de Ste Gême; History - United States / Histoire - États-Unis (UMI : 0337); Jean Boze; Louisiana; Louisiane; New Orleans; Nouvelle-Orléans; Saint-Domingue; Saint-Domingue refugee; United States; XIXe siècle; atlantique français; histoire; histoire de l'atlantique; history; identity; identité; réfugiés de Saint-Domingue; États-Unis; émigré

Jacques-Pierre Brissot, Étienne Clavière et la libre Amérique : du gallo-américanisme à la mission Genet - Corriveau, Tamara (Université de Montréal, 2008)
Keywords: American revolution; Commerce; Enlightenment; French revolution; Liberalism; Liberty; Liberté; Libéralisme économique; Lumières; Moeurs; Morality; Moralité; Republicanism; Républicanisme; Révolution américaine; Révolution française

Débats contemporains dans l’historiographie de la Révolution haïtienne - Grou, Élizabeth (Université de Montréal, 2014)
L’historiographie de la Révolution haïtienne est en plein essor depuis les vingt dernières années. Il existe désormais un large éventail d’interprétations sur les événements qui mènent à la création d’Haïti. L’objet de ce mémoire est d’exposer différentes perspectives sur des questions qui demeurent cruciales dans l’historiographie contemporaine. Le mémoire est divisé en trois sections. Chacun des chapitres développe une problématique particulière de l’historiographie en mettant en parallèle les conclusions de différents chercheurs. Le premier chapitre est consacré au thème de la transformation de la révolte en révolution. Ensuite, il sera question de l'impact de la Révolution haïtienne sur l'histoire de l'esclavage dans le monde atlantique. Pour conclure, la dichotomie entre l’absence de longue date de la Révolution haïtienne dans l’historiographie occidentale et l’attention qu’elle reçoit aujourd’hui sera examinée dans le troisième chapitre. Aujourd’hui, la réécriture de la Révolution haïtienne est très populaire et attire des chercheurs de différents milieux. C’est dans ce contexte que ce mémoire présente une mise en perspective des principaux débats idéologiques de l’historiographie de la Révolution haïtienne depuis les années quatre-vingt-dix.
Keywords: Abolition; Cause; Contemporain; Contemporary; Debate; Débat; Esclavage; Haiti; Haitian; Haïti; Haïtienne; Historiographie; Historiography; History - Black / Histoire des Noirs (UMI : 0328); Impact; Revolution; Révolution; Slavery

De la tyrannie en Amérique : étude des sources de l'interprétation pessimiste de l'oeuvre de Tocqueville dans les sciences sociales américaines d'après-guerre - Harmon, Jonathan (Université de Montréal, 2008)
Keywords: Arendt; De la démocratie en Amétique; Democracy in America; Hartz; Individualism; Individualisme; Kirk; Nisbet; Riesman; Tocqueville; Totalitarism; Totalitarisme; Welfare State; État Providence

L’interaction entre l’opinion publique et la diplomatie françaises au moment de la guerre d’Indépendance américaine - Lagrange, Marianne (Université de Montréal, 2017)
Dès les batailles de Lexington et Concord le 19 avril 1775, la guerre d’Indépendance américaine retient l’attention en France, et ce, à la fois des diplomates français, mais également de l’opinion publique française. Parmi les deux groupes, on retrouve des éléments qui tentent de favoriser et de préparer une intervention officielle de la France dans cette guerre. L’objectif de ce mémoire est donc d’étudier l’interaction qui eut alors lieu entre l’opinion publique et la diplomatie. Le premier chapitre étudie comment l’opinion publique crée les conditions opportunes à l’intervention de Beaumarchais auprès du gouvernement français, puis l’impact de cette intervention. Le second chapitre s’intéresse quant à lui aux arguments mis de l’avant par le ministère des Affaires étrangères – par l’entremise de sa propre gazette, les Affaires de l’Angleterre et de l’Amérique – pour convaincre et préparer l’opinion publique à l’intervention de la France dans la guerre d’Indépendance américaine.
Keywords: Affaires de l'Angleterre et de l'Amérique; American War of Independence; Diplomacy; Diplomatie; France; Guerre d'Indépendance américaine; History - European / Histoire - Européenne (UMI : 0335); Opinion publique; Pierre-Augustin Caron de Beaumarchais; Public opinion; United States; États-Unis

Les relations diplomatiques franco-américaines lors de l'expédition du général Leclerc : le commerce, le territoire, la race et l'opinion. 1800-1804 - Simard, Guillaume (Université de Montréal, 2008)
Keywords: Colonialisme - France; Commerce - États-Unis; 1800-1804; Diplomatie France - États-Unis; Opinion populaire - États-Unis; 1800-1804; Relations raciales - États-Unis; Révolution haïtienne; Territoire États-Unis; 1800-1804

Under the roof and the pen of Elizabeth Willing Powel. Material culture, sociability, and letters in revolutionary and early republican Philadelphia - Templier, Sarah (Université de Montréal, 2014)
Set in late eighteenth-century Philadelphia, covering the American revolutionary and the early republican eras, this thesis explores three major and interrelated themes: material culture, sociability, and female agency. It focuses on Elizabeth Willing Powel, a privileged and educated woman of Philadelphia, and on the ways she projected herself to society through the material environment of her house –Powel House - and through her correspondence. Elizabeth Powel was renown for her intellect, her conversations and her hostess qualities. This project explores the interaction between an elite woman and her material environment during the eventful revolutionary and post-revolutionary era, and how material culture conveyed a social, cultural and political stance. By a careful analysis of Elizabeth Powel's correspondence - with a particular attention to her discourse on women's social role, female education, politics, and goods - this thesis observes Elizabeth's social interactions and self-presentation to society. It also explores how material culture and epistolary activities provided Elizabeth with means of agency, and ways to participate to late eighteenth-century American society, then undergoing crucial transformations.
Keywords: Elizabeth Willing Powel; George Washington; History - United States / Histoire - États-Unis (UMI : 0337); Philadelphia; Philadelphie; Powel House; agentivité féminine; culture matérielle; dix-huitième siècle; eighteenth-century; elite; epistolary writing; feminine agency; material culture; sociability; sociabilité; écriture épistolaire; élite

It runs in the family : the Bradfords, print, and liberty (1680-1810) - Tourangeau, Catherine (Université de Montréal, 2014)
En se basant sur l’histoire des Bradfords, l’une des plus grandes familles d’imprimeurs de l’histoire américaine, ce mémoire étudie la relation entre l’imprimé, les imprimeurs, et divers discours sur la liberté au cours du « long » 18e siècle. Il retrace la transition entre une ère de la « liberté de parole, » née des débats sur la liberté de presse et d’expression de la période coloniale, et une ère de la « parole de la liberté, » née au cours de la Révolution et entretenue sous la jeune république. Cette transition fut le produit de la transformation du discours des contemporains sur la liberté, mais s’effectua également en lien avec la transformation du milieu de l’imprimerie et de la culture de l’imprimé. Selon les circonstances politiques, sociales, économiques et culturelles particulières des périodes coloniale, révolutionnaire, et républicaine, l’imprimé et les imprimeurs américains furent appelés à disséminer et à contribuer au discours sur la liberté. Ils établirent ainsi une forte association entre l’imprimé et la liberté dans la culture de l’imprimé du 18e siècle, qui était destinée à être transmise aux siècles suivants. Mots-
Keywords: 18e siècle; 18th century; Book history; Culture de l'imprimé; Histoire du livre; History - United States / Histoire - États-Unis (UMI : 0337); Imprimeurs; Journaux; Newspapers; Opinion publique; Print culture; Printers; Public opinion

Henry C. Carey et le système américain d’économie contre l’impérialisme du libre-échange britannique : son passage au New York Tribune - Vézina, Simon (Université de Montréal, 2015)
Les débats économiques au 19e siècle, loin d’être l’apanage du monde universitaire, étaient aux États-Unis un des principaux objets de contentieux entre les partis politiques et ceux-ci trouvaient écho dans la sphère publique. Les journaux étaient alors le principal moyen de communiquer les opinions des différents partis. La présente étude vise à mettre en contexte et cerner la position des écrits du plus important économiste américain de son époque, Henry Charles Carey (1793-1879), reconnu comme tel par J.S. Mill et Karl Marx en leur temps, lors de la décennie de 1850 dans le journal le plus influent de cette période, le New York Tribune. Pour ce faire, il a fallu au préalable identifier les articles non signés de Carey dans le journal, ce qui n’avait auparavant jamais été fait. Au moment d’écrire dans le principal organe américain qui défendait la protection aux États-Unis afin d’industrialiser le pays, Carey était alors le représentant le plus prééminent du système américain d’économie. Ce dernier, fondé sur les écrits d’Alexander Hamilton, prônait l’industrialisation des États-Unis et l’intervention de l’État pour défendre le bien commun, s’opposant ainsi à l’école libérale anglaise basée sur les écrits d’Adam Smith. Conceptuellement, la pensée économique de Carey se situe dans la tradition des Autres Canon, basée sur la production et l’innovation. Ceci le mena à s’opposer avec vigueur tant au malthusianisme qu’à la division internationale du travail, justifiée théoriquement par la thèse de l’avantage comparatif de Ricardo. En effet, dans son analyse, la volonté exprimée au milieu du 19e siècle par l’Angleterre de devenir l’atelier du monde et de faire du reste des nations des producteurs de matières premières sous un régime de libre-échange n’était rien d’autre que la continuation de la politique coloniale par d’autres moyens. Pour Carey, la spécialisation dans l’exportation de matières premières, notamment défendue par les planteurs du Sud des États-Unis, loin d’être bénéfique au pays, était le sûr gage de la pauvreté comme les cas de l’Irlande et de l’Inde le démontraient.
Keywords: British Empire; Economics - History / Économie - Histoire (UMI : 0509); Empire britannique; United States; croissance économique; economic growth; free trade; imperialism; impérialisme; libre-échange; newspaper; presse; protectionism; protectionnisme; États-Unis

Entangling the Quebec Act: Transnational Contexts, Meanings, and Legacies in North America and the British Empire - Hubert, Ollivier; Furstenberg, François (McGill-Queen's University Press, 2020)
Section: viii, 401 pages : illustrations, cartes ; 23 cm

L'alimentation des esclaves d'origine africaine de la Basse-Louisiane française (1724-1751) : une fenêtre sur les rapports de pouvoir dans une société de frontière esclavagiste - Jacques-Côté, Ariane (Université de Montréal, 2011)
By studying practices related to slave food in French Louisiana, we learn more about solidarities and conflicts between social groups and within these groups in a slave frontier society. The first chapter is about two main strategies of whites related to slave food: to preserve the slave population and to control their participation in the economy. The second chapter is about the roles of slaves in the food economy, as specialized workers and as producers and distributors of food; these roles enable them to gain more autonomy within the colonial society. The different strategies of slaves in the area of food are at the heart of conflicts and of solidarity between them.
Keywords: Alimentation; Esclavage; Food; History - United States / Histoire - États-Unis (UMI : 0337); Louisiana; Louisiane; Slavery

Saint-Domingue Refugees and their Enslaved Property : Abolition Societies and the Enforcement of Gradual Emancipation in Pennsylvania and New York - St-Louis, Katherine Anne (Université de Montréal, 2016)
This thesis explores the role of abolition societies in the enforcement of gradual eman-cipation in the north of the United States in the late-eighteenth century. More specifically, it focuses on the refugees from Saint-Domingue who brought their slaves in the state of Penn-sylvania and New York, and how abolition societies adapted their strategies to cope with the massive arrival of hundreds of these refugees in the 1790s. The first section discusses the gradual end of slavery in the north following the American Revolution, starting with Pennsyl-vania in 1780, and the emergence of abolition societies, especially the Pennsylvania Abolition Society (PAS) and the New-York Manumission Society (NYMS). In addition, this section considers the strategies of anti-slavery activists to promote and protect gradual emancipation and limit the movement of slaves within and without their respective states. The second sec-tion presents a case study of Saint-Domingue refugees coming with their slaves and how they interacted with residual slavery in New York and Pennsylvania. It also illustrates how maneu-vers employed by West-Indian slave owners in order to keep their slaves often failed as a re-sult of the intervention of abolition societies.
Keywords: Abolitionists (United States); Abolitionnistes (États-Unis); Dix-huitième siècle; Eighteenth Century; Gradual emancipation; Haitian Revolution (1791-1804) – Refugees; History - United States / Histoire - États-Unis (UMI : 0337); New York; Pennsylvania; Pennsylvanie; Révolution haïtienne (1791-1804) – Réfugiés; Émancipation graduelle